ERSPECTIVE OF SENTENCING GUIDELINES IMPLEMENTATION IN CONTINENTAL LAW SYSTEM - Rasim, Babanly (Review of European and Comparative Law, 2020)
The article examines the positive and negative aspects of the existence of sen-tencing guidelines in different legal systems, as well as the reasons and purpose of implementing the relevant guidelines . Analyzed aspects that lead to the conclu-sion of feasibility or unreasonableness implementation of sentencing guidelines in continental law system and it is proved the absence of obstacles for the implemen-tation of the said sentencing guidelines in such a legal system for